Capacidade inovativa, seus antecedentes e o desempenho de empresas brasileiras inovadoras - Miranda, Kléber Formiga (2012)
The maintenance and development of organizational competitiveness have motivated several studies in order to detect, in the innovation, determinants to business performance. Approaches such as theory of the firm and RBV assign to the company the role to generate continuous, endogenously, the best performance to maintain its competitive market advantage. The main objective of this study is to analyze the relationship between innovative capacity, as well as its antecedents, and the innovative performance of innovative Brazilian companies. The three research hypotheses seek to confirm the relationship between the antecedents of innovative capacity, innovative capacity and performance of companies. The research methodology is characterized as exploratory, with a quantitative approach, using statistical techniques of correlation and linear regression. The research population, chosen among the publicly traded companies, classified in the sectors covered by the criteria of IBI, amounted to 174 companies properly analyzed and listed to be sent to the IBGE, where was found the number of 73 that participated in the PINTEC editions of 2005 and 2008, constituting the research sample. To measure the innovative capacity and its antecedents were used PINTEC data. The variables components of innovative capacity were composed of product innovation, process, organizational and marketing. The variables of the antecedents of innovative capacity contained investments by companies in support of acquiring external knowledge, activities with R&D (internal and external), acquisition of equipment and machinery, training, introductions of innovations and new projects. The business performance, measured from the economic, operational and value dimensions, was as variable ROA, EBITDA and MVA®, respectively, whose values were obtained by variables of Economática®. The made relationships considered the one-year lag between the variables of innovation and performance, from the perspective of maturity of investment and innovative capacity in this meantime. The results of H1 indicated the existence of a positive relationship between the antecedents of innovative capability and innovative capability, suggesting, however, significant investments in the antecedents for the generation of innovative capacity. The results of H2 revealed a positive relationship between the antecedents of innovation and the economic and operational performance, being not significant in relation to the MVA®. About H3, no evidence can be inferred about the relationship between the innovative capacity and economic and operational performances, being possible to observe its relationship with MVA®. It is concluded that the operational and economic performance of the companies analyzed are magnified when there are investments in software and innovates in completely new products for the company and for the national market, directing the precepts of the theory of the firm because they relate to strategic investments in generation innovative capacity. The generation of shareholder value is maximized with investments that boost marketing and process innovation, because the innovative capacity strategic business measured by these types of innovation contributes to the maintenance of strategic differentiation of companies, as proposed by the RBV.